SÖZLÜ VE YAZILI KÜLTÜR AYRIMINDA KUR’AN - Süleyman Gezer (İslami İlimler Dergisi)
It is known that the Quran is revealed to Arabians who are living in verbal culture, its a usual situation that the Quran conveys elements belonging to verbal culture and verbal language in its expressions and styles. This article mostly consists of the processes that take place in the understanding of the Quran and the transition of it from verbal culture to written culture. The Quran is revealed through the Arabic language. Quran is a distinctive text which provides transition between verbal and written cultures.